Transparent (1–x)TiO2–xFe2O3 (x = 0, 5, 10, 15 and 20 mol%) thin films prepared by sol-gel process - Hwang, Kyu-Seog; Jeon, Young-Sun; Jeon, Kyung-Ok; Kim, Byung-Hoon (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Transparent iron-doped titanium oxide thin films were prepared on soda-lime-silica glass substrate from a titanium naphthenate precursor. Films prefired at 500°C for 10 min were finally annealed at 500°C for 30 min in air. Field emission–scanning electron microscope and scanning probe microscope were used for characterizing the surface structure of the film. A sharp absorption edge of the film was observed. The film containing iron showed a shift towards the visible in the absorption threshold.
Optica Applicata, Vol. 35, 2005, nr 2, s. 191-199
Keywords: optyka; titanium oxide; thin film; iron